Mikrostruktur dan Karakteristik Permukaan Kayu Pinus Scots (Pinus sylvestris L.) Termodifikasi Gliserol dan Asam Sitrat - Gabriel Tobing; Nurul Sofiaturizkiyah; Efrida Basri; Resa Martha; Istie Rahayu; Philippe Gérardin; Wayan Darmawan (Institut Pertanian Bogor, 2024)
Scots pine (Pinus sylvestris L.) wood is one of the most popular timber export products. However, its low durability can reduce the potential and utilization of the wood. Chemical modification is one of the solutions to overcome this drawback. Chemical modification using non-biocide materials such as glycerol and citric acid was carried out to improve the inferior properties of wood. The study aimed to observe the microstructure and evaluate the surface characteristics of glycerol and citric acid-modified scots pine wood. Scots pine wood was modified using glycerol and citric acid with weight percent gain (WPG) values of 20% and 46%. Surface characteristics were measured, including surface roughness, surface free energy (SFE), wettability, and bonding quality. The results show that chemical modification using glycerol and citric acid resulted in the structure of the pine wood being more filled and denser. The modification could also reduce the roughness of the wood surface, resulting in decreased SFE value, increased contact angle, and decreased wettability on the wood surface. It might cause a decrease in the bonding quality because the wood did not have the strength to mechanically lock with the paint. Glycerol and citric acid modified-scots pine wood can be considered for exterior application. Keywords: citric acid, glycerol, microstructure, scots pine, surface characteristics